THE IMPLEMENTATION OF JIGSAW TECHNIQUE IN TEACHING READING COMPREHENSION - Mutaqin, Jaenal; Haryudin, Acep (IKIP Siliwangi, 2020)
Reading is considered an important aspect for students because of its valuable benefits in developing knowledge. In English, one of the skills that must be mastered is reading skill. However, to comprehend the contents of the text well there were still many students who find it difficult, it is caused by inappropriate technique used by teachers in teaching English. Therefore, to improve their reading comprehension proper technique must be applied. The aim of this reseach is to investigate whether there was an improvement by using jigsaw technique in students' reading comprehension in eighth grade students at SMPN 2 Pasirkuda. The researcher used 33 students as a sample of this research using a pre-experimental design. The research instrument used a test in the pre-test and post-test. The result of this research presents that using jigsaw technique had the positive effect in improving reading comprehension. We can see the results from paired samples t-test that there is a significant difference for the pre- test score (M = 47.45, SD = 7,55) and post-test (M = 68.85, SD = 6,38), t (32) = -19,40, p <0.05. It concluded that the jigsaw technique improve the students’ reading comprehension. Keywords: Jigsaw Technique, Reading Comprehension